2019
DOI: 10.3389/fonc.2019.01082
|View full text |Cite
|
Sign up to set email alerts
|

External Replication of Urinary Bladder Cancer Prognostic Polymorphisms in the UK Biobank

Abstract: Introduction: Multiple studies have reported genetic associations with prognostic outcomes of urinary bladder cancer. However, the lack of replication of these associations prohibits establishing further evidence-based research directions. Moreover, there is a lack of independent bladder cancer patient samples that contain prognostic measures, making genetic replication analyses even more challenging.Materials and Methods: We have identified 1,534 eligible patients and used data on Hospital Episode Statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Also, the rs2042329 T allele was related to significantly higher expression levels of CWC27 among tumor tissues in low- or high-grade non-muscle-invasive tumors, rather than in the adjacent normal tissues and invasive tumors. A replication study in the UK population [ 33 ] also showed that rs2042329 was linked to an increased risk of urinary BCa recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the rs2042329 T allele was related to significantly higher expression levels of CWC27 among tumor tissues in low- or high-grade non-muscle-invasive tumors, rather than in the adjacent normal tissues and invasive tumors. A replication study in the UK population [ 33 ] also showed that rs2042329 was linked to an increased risk of urinary BCa recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…FKBP1A has also been reported to play a role in promoting tumor progression. Zhang et al (2019) found that FKBP1A affected the proliferation and migration of prostate cancer cells ( Lipunova et al, 2019 ). Romano et al (2008) found that knockdown of FKBP1A can activate the TGF-β signaling pathway in chronic lymphocytic leukemia cells ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…New strategies for disease prevention have comprised the exploration of gene-environment interactions and the attenuation of genetic risk via health-promoting factors (21)(22)(23). Previous studies have investigated the interaction between the genetic factors of AD and environmental variables, such as diet, alcohol, smoking, and pollutants (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%